Projection operators on matrix weighted L^p and a simple sufficient Muckenhoupt condition - Nielsen, Morten; Rasmussen, Morten Grud (MATHEMATICA SCANDINAVICA, 2018)
Boundedness for a class of projection operators, which includes the coordinate projections, on matrix weighted L^p-spaces is completely characterised in terms of simple scalar conditions. Using the projection result, sufficient conditions, which are straightforward to verify, are obtained that ensure that a given matrix weight is contained in the Muckenhoupt matrix A_p class. Applications to singular integral operators with product kernels are considered.